The effect of some plants extracts on Trichomonis Vaginalis - Ghanim Abdulwahabl, Entesar; Mahmod Yaseen, Enas; Ibraheem alalosy, Tawfeek (Tikrit Journal of Pharmaceutical Sciences, 2023)
This is is an experimental study aimed to study the effect of three plants extracts on the activity of the Trichomonis vaginalis parasite. After isolation of the parasite and growing on CPLM media, six plant extracts three of them were water extracts and others were alcoholic extracts which were prepared from Artemisia herba alba, Punica grantum and Capparis spinosa respectively were added to parasite media. Study of parasite activity and grorvth after24,48,96,72 hours were observed. the Artemisia herba alba 'alcoholic extract had good suppression effect through 24 hours at 0.5'olo concentration while the same extract from Ptmica granatum at 0.5Yo concentration also affected the parasite through 48 hours and Capparis spinosa alcoholic extract inhibited the parasite activity in l%o concentration through 48 hours .The water extract for Artcmisia herba alba had better inhibition elfect through 48 hours at 0.5Yo concentration .Punica granatum affected through 24 hours but at l7o concentration, while Capparis water extract had no effect. We concluded that Artemisia herba a/64 alcoholic extract had better eflfect than others and rve recommended further studies to extract the active substances of medical plants for the treatment of Trichomonas vaginalis